1990
DOI: 10.1073/pnas.87.5.1965
|View full text |Cite
|
Sign up to set email alerts
|

Pahhph-5: a mouse mutant deficient in phenylalanine hydroxylase.

Abstract: Mutant mice exhibiting heritable hyperphenylalaninemia have been isolated after ethylnitrosourea mutagenesis of the germ line. We describe one mutant pedigree in which phenylalanine hydroxylase activity is severely deficient in homozygotes and reduced in heterozygotes while other biochemical components of phenylalanine catabolism are normal. In homozygotes, injection of phenylalanine causes severe hyperphenylalaninemia and urinary excretion of phenylketones but not hypertyrosinemia. Severe chronic hyperphenyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
82
1

Year Published

1993
1993
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(87 citation statements)
references
References 25 publications
4
82
1
Order By: Relevance
“…Shortly after birth (P4), the pups chosen from the remaining a-methylphenylalanine + Phe litters (group 1) weighed roughly 20% less than pups chosen from the other litters [mean weights = 8.3 f 0.8 gm (group l), 10.0 f 1.3 gm (group 2), 10.2 + 1.6 gm (controls); F(1,32) = 17.05, p < 0.0003, regression analysis of P4 weights in group 1 vs the other two groups]. This difference in infant mortality and weight is similar to that reported by others (e.g., Kerr et al, 1968;Brass et al, 1982;McDonald et al, 1990), and occurred despite the yoking of food intake. By P 12 the difference in weight among the groups of rat pups had disappeared.…”
Section: Resultssupporting
confidence: 78%
“…Shortly after birth (P4), the pups chosen from the remaining a-methylphenylalanine + Phe litters (group 1) weighed roughly 20% less than pups chosen from the other litters [mean weights = 8.3 f 0.8 gm (group l), 10.0 f 1.3 gm (group 2), 10.2 + 1.6 gm (controls); F(1,32) = 17.05, p < 0.0003, regression analysis of P4 weights in group 1 vs the other two groups]. This difference in infant mortality and weight is similar to that reported by others (e.g., Kerr et al, 1968;Brass et al, 1982;McDonald et al, 1990), and occurred despite the yoking of food intake. By P 12 the difference in weight among the groups of rat pups had disappeared.…”
Section: Resultssupporting
confidence: 78%
“…Three mouse Pah mutations have been artificially created: Pah enu1 [McDonald et al, 1990]; Pah enu2 ; and Pah enu3 [Shedlovsky et al, 1993]. The Pah enu3 allele is now historic.…”
Section: Mouse Modelsmentioning
confidence: 99%
“…The Pah enu2 mouse is a suitable model to study PKU as it exhibits similar clinical characteristics as human patients that include hyperphenylalanemia, hypopigmentation (5,6), and cognitive defects. Cabib et al (7) found these mice to have cognitive deficits that involve spatial and nonspatial recognition that is separate from motor impairment and not related to emotional reactivity to novel situations.…”
mentioning
confidence: 99%